Auditoría financiera y su incidencia en la presentación de los estados financieros de la empresa Agroservicio Jiménez del cantón Quinsaloma período 2021 - 2022 - Moyano Vergara , Mariuxi Angélica (2024)
his research project focused on carrying out a financial audit to verify the impact on the presentation of the financial statements of Agroservicio Jiménez for the 2021-2022 period. Focusing its methodology on the positivist paradigm under a non-experimental descriptive quantitative approach; which made it possible to obtain information on the perception of the analysis unit made up of four people, including the manager and general workers, through a survey and the development of the phases of the Audit, it was obtained that the company lacks accounting policies, a manual of functions and procedures and a reliable accounting system, findings that qualified all areas at a high risk level and an unreliable internal control system, however, the application of indicators indicate a stable position of the company. As a consequence, it is concluded that there is an erroneous perception of the financial health of the company since the value of assets is being overvalued and expenses are being underestimated.